Modem Communications Systems Development Guidelines in Function of Air Traffic Safety ... - Obradović, Petar; Flatz, Leon; Ljubičić, Perica (Promet - Traffic&Transportation)
The communications requirements in air traffic control areincreasing in complexity. From the middle 90s, huge progress inairport infrastructure, especially in air traffic control systems,has been made in Bosnia and Herzegovina in damage rehabilitation,caused by war conflicts, owing, first of all, to the EuropeanUnion aid that contributed to the re-establishment of regularinternational air traffic. The current air traffic control systemhas matured in its functionality. Therefore, the phase of advancementand preparation for the technological improvementis the next logical step. However, before establishing a new communicationsstrategy, the current application trends have to beanalyzed in details according to the existing communicationsenvironment interfaces. The goal of this work is to find theguidelines of technological development that will result in moreefficiency, safety and economic benefit in the near future, butthe air traffic safety must not be compromised by economicbenefit.